Biomass production and nutrient content in different Eucalyptus genotypes in Pampa Gaucho, Brazil - Santos, Kristiana Fiorentin dos; Ludvichak, Aline Aparecida; Queiroz, Tulio Baroso [UNESP]; Schumacher, Mauro Valdir; Araujo, Elias Frank de (Univ Federal Rural Pernambuco, 2019)
The objective of this study was to estimate the biomass, nutrient stocks, and simulate the export of nutrients, in different genotypes of Eucalyptus. The experiment was conducted in Sao Gabriel, RS, Brazil, in 43-month-old stands. The selected trees were fractionated into leaves, branches, stembark and stemwood. An estimate of nutrient exports by biomass was calculated for three scenarios. The amount of total biomass ranged from 33.68 to 84.00 Mg ha(-1), with the highest production being E. uroglobulus, and E. dunnii the lowest. The tree canopy accumulated between 47% and 65% of the total macronutrients and 46% to 67% of the total micronutrients (E. benthamii (P2) and E. urograndis). The highest amount of nutrients exported with biomass harvesting, for the first and second scenario (harvesting the stemwood and harvesting the stemwood with stembark), occurred in E. uroglobulus (N, K, and S), E. urograndis (P, Mg, and Cu) and E. saligna (Fe, Zn, and B). For the third scenario (stem and canopy), the highest nutrient exportation occurred in E. urograndis, except for S, where the highest removal occurred in E. uroglobulus. The harvesting of only the stemwood resulted in the removal of the least nutrients from the system, independent of the genotypes.
Keywords: clonal Eucalyptus; forestry nutrition; silviculture; sustainability